Legal construction of beneficial owner liability for violations of medical hazardous waste management in hospitals - Widiyanto, Teguh Prastyo Nur; Budiono, Abdul Rachmad; Djumikasih, Djumikasih; Kasyafi, Haidar Fikri (Graduate School of Universitas Brawijaya, 2026)
Patient safety should be positioned as the primary normative framework in analyzing responsibility for hazardous medical waste management in hospitals. Modern health law recognizes that patient safety extends beyond clinical competence to encompass the entire institutional system within which healthcare services are provided. Hospitals have a legal obligation to establish and maintain a safe care environment, including infection control, environmental hygiene, and hazardous waste management. However, in modern hospital governance, strategic decisions are often influenced by parties that exercise effective control but are not formally registered as directors or shareholders. However, legal regulations in Indonesia still tend to place responsibility on legal entities and operational implementers, potentially creating an accountability gap. This study uses normative legal methods with legislative, conceptual, and doctrinal approaches. Legal material is analyzed from a descriptive perspective to formulate a legal responsibility construct oriented toward the substance of patient safety control and protection. The research findings indicate that beneficial owners of a hospital can be held legally liable if they are proven to have control or influence over hazardous medical waste management policies. This liability structure can be established through the application of the doctrines of corporate breach of the veil, vicarious liability, and strict liability. In conclusion, beneficial owners can be held legally liable when they exercise effective control over policies that endanger patient safety. This approach enhances patient protection and promotes transparent, accountable, and fair hospital governance.